Acute Anterior Choroidal Artery Territory Infarction: A Case Series Report - Antonia Tsika; Polyxeni Stamati; Zisis Tsouris; Antonios Provatas; Alexandra Papa; Dimitrios Tsimoulis; Stylliani Ralli; Vasileios Siokas; Efthimios Dardiotis (MDPI AG, 2024)
Due to the occlusion of the anterior choroidal artery (AChA), ischemic strokes are described with the classic clinical triad, namely hemiplegia, hemianesthesia, and homonymous hemianopsia. The aim of this study is to document the characteristic clinical presentation and course of AChA infract cases. We describe five cases with acute infarction in the distribution of the AChA, admitted to the Neurological Department of the University General Hospital of Larissa. Results: All cases presented with hemiparesis and lower facial nerve palsy, while four of them had dysarthria, and two patients exhibited ataxia. Two cases underwent intravenous thrombolysis. A notable feature was the worsening of the clinical course, specifically the exacerbation of upper limb weakness within 48 h. Stabilization occurred after the third day, with the final development of a more severe clinical presentation than the initial one. Additionally, muscle weakness was more severe in the upper limb than in the lower limb. The recovery of upper limb function was poor in the three-month follow-up for the four cases. While vascular brain episodes are characterized by sudden onset, in AChA infraction, the clinical onset can be gradually developed over a few days, with a greater burden on the upper limb and poorer recovery.